Synthesis and characterisation of nanometric simulated nuclear fuel (SIMfuel) - Bergström, Julia (My University, 2024)
In this project a procedure for the synthesis of Ce(III) and La(III) doped UO2 SIMfuel was tested. The methods include electrochemical reduction of aqueous U(VI), Ln-doping, co-precipitation of nanometric doped UO2 powder, and pressing and sin tering of pellets. The aim was to synthesise SIMfuel with a high degree of dopant homogeneity and a nanometric grain structure found in irradiated uranium fuel with high burn-up structure. Four nanometric pellets were made, two with no dopants, one with 1% La, 1% Ce and one with 1% La, 5% Ce. Reference pellets were also made through U(VI) reduction in high temperature H2 atmosphere. Elemental com position, unit cell dimensions, density, porosity, grain size and dopant homogeneity were characterised for nanometric pellets and reference pellets. Both types of pellets were found to have good homogeneity of dopants at both doping levels. The grain size for the nanometric pellets were found to not actually be nanometric, with a size range of around 1-25 µm. It is assumed that the high temperature sintering caused significant grain growth for the nanometric pellets.
Keywords: SIMfuel; Ln-doped UO2; Electrochemical reduction; co-precipitation